EARLY LIFE HISTORY OF STOLEPHORUS SP. (S. MACROPS?) FROM VELLAR ESTUARY, PORTO NOVO - Thangaraja, M (Indian Journal of Fisheries, 2011)
Early life history of an unidentified species of Stolephorus {Stolephorusmacrops?) was studied, rearing five earlier stages in the laboratory and collectingthe subsequent postlarvae and juvenile (6 stages) from the plankton. The eggs hadoccurred in the marine zone of the estuary (salinity 32.58-33.37 %=) during February-March. The larvae were common in zones ranging in salinity from 15.35 %•>to 33.37 %.. during March-April. The different stages are illustrated.